SYNTHESIS OF COPPER OXIDE NANOPARTICLES BY CHEMICAL PRECIPITATION METHOD FOR THE DETERMINATION OF ANTIBACTERIAL EFFICACY AGAINST STREPTOCOCCUS SP. AND STAPHYLOCOCCUS SP. - SHRADDHA SHIRSAT; DHANASHRI PAWAR; NISHITA JAIN; JAYANT PAWAR; VIDYA S TALE; RABINDER HENRY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: To determine antimicrobial efficacy of copper oxide nanoparticles (CuO NPs) against Streptococcus sp. and Staphylococcus sp. Methods: CuO NPs were synthesized using chemical precipitation method. The reducing agent, 0.1 M NaOH, was used along with 100 mM CuSO4 precursor for the synthesis of CuO NPs. The characterization of CuO NPs was done by ultraviolet-visible spectroscopy and scanning electron microscopy (SEM) to study optical and morphological characteristics, correspondingly. The identification of bacterial cultures was done through microscopic and biochemical studies. Antibacterial efficacy of CuO NPs was determined against Streptococcus sp. and Staphylococcus sp. by qualitative and quantitative methods through anti-well diffusion assay and broth dilution method, respectively. Results: The absorption spectrum and band gap were found to be at 260 nm and 4.77 eV, respectively. The SEM image of CuO NPs shows cluster of nanostructures having width of individual clusters in the range of 100 nm–500 nm. CuO NPs showed inhibition at a concentration ranging from 60 μg/mL to 1000 μg/mL. Conclusion: Finally, CuO NPs can be used as effective antibacterial agent against Streptococcus sp. and Staphylococcus sp. and may have applications in medical microbiology.